ANALYSIS OF ANATOMICAL ELEMENTS AS WOOD TEXTURE CHARACTERISTICS - Bardarov, Nikolai; Christoff, Nicole; Todorov, Vladislav; Antov, Petar; Kaludova, Mariana (Innovation in Woodworking Industry and Engineering design, 2021)
In recent years, more and more systems for computer recognition of tree species are entering, which show good results in solving a certain group of problems. Some of them have already proven themselves in solving such tasks as quality control of wood materials. Studies also show that the classifications of tree species used so far do not allow to solve more general problems of structural wood science. The approaches, methods and means used in computer recognition for modeling the structure of the wood presuppose such a classification of the tree species, which should be based on a more general view on the structure of the wood in comparison with the methods used so far. This would allow to study and describe in a single formalized classification scheme all the anatomical elements that are observed with the corresponding increase in the samples of tree species. In addition, it is necessary to specify the term "texture", applicable in the computer structural anatomy of wood for the purposes of using the methods of computer vision. The paper discusses the initial results of research related to the application of the requirements of computer modeling in solving some problems of wood anatomy. In particular, recommendations have been made for the quantitative characteristics of the study region in the wood samples and for the description of the anatomical elements making up the wood that will fall into this region and can be examined with sufficient accuracy.